Gut microbiota alternation with training periodization and physical fitness in Japanese elite athletes - Akazawa, N.; Nakamura, M.; Eda, N.; Murakami, H.; Nakagata, T.; Nanri, H.; Park, J.; Hosomi, K.; Mizuguchi, K.; Kunisawa, J.; Miyachi, M.; Hoshikawa, M. (Frontiers in Sports and Active Living, 2023)
Introduction: The gut microbiome plays a fundamental role in host homeostasis through regulating immune functions, enzyme activity, and hormone secretion. Exercise is associated with changes in gut microbiome composition and function. However, few studies have investigated the gut microbiome during training periodization. The present study aimed to investigate the relationship between training periodization and the gut microbiome in elite athletes.